2020
DOI: 10.5946/ce.2019.175
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Ultrasound-Guided Random Omental Fine Needle Aspiration: A Novel Technique for the Diagnosis of Peritoneal Carcinomatosis

Abstract: This pilot, single arm prospective uncontrolled study, was conducted at a tertiary hospital in New Delhi from October 2015 to April 2017. The study was approved by the institutional ethics committee. Consecutive patients with ascites and known or suspected malignancy, who underwent EUS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…From another prospective study by Singh P et al, EUS also showed a better sensitivity compared to that of CT in the diagnosis of small liver lesions (40% vs. 19%; p = 0.008) [ 27 ]. EUS has a better accuracy in detecting minimal ascites or omental thickening in pancreatic carcinoma, and sampling can be performed withing the same session for the detection of metastases to avoid futile surgeries [ 28 , 29 ]. Similarly, a diagnosis of perivascular cuffing suggestive of extravascular migratory metastases (EVMMs) can be made via EUS.…”
Section: Role Of Eus In the Staging Of Tumorsmentioning
confidence: 99%
“…From another prospective study by Singh P et al, EUS also showed a better sensitivity compared to that of CT in the diagnosis of small liver lesions (40% vs. 19%; p = 0.008) [ 27 ]. EUS has a better accuracy in detecting minimal ascites or omental thickening in pancreatic carcinoma, and sampling can be performed withing the same session for the detection of metastases to avoid futile surgeries [ 28 , 29 ]. Similarly, a diagnosis of perivascular cuffing suggestive of extravascular migratory metastases (EVMMs) can be made via EUS.…”
Section: Role Of Eus In the Staging Of Tumorsmentioning
confidence: 99%